What can clinicians do to improve outcomes across psychiatric treatments: a conceptual review of non-specific components. (2020) - Priebe, S.; Conneely, M.; McCabe, R.; Bird, V.
Abstract: Aims: Psychiatric treatments have specific and non-specific components. The latter has been addressed in an extensive literature on the placebo-effect in pharmacology and on common factors in psychotherapy. In the practice of mental health care, pharmacological, psychotherapeutic and social treatments are combined in complex interventions. This paper aims to review non-specific components across diverse psychiatric treatments and consider implications for practice and research. Methods: We conducted a non-systematic review of non-specific components across psychiatric treatments, their impact on treatment processes and outcomes, and interventions to improve them. Results: The identified research is heterogeneous, both in design and quality. All non-specific components capture aspects of how clinicians communicate with patients. They are grouped into general verbal communication – focusing on initial contacts, empathy, clarity of communication, and detecting cues about unspoken concerns – non-verbal communication, the framing of treatments and decision-making. The evidence is stronger for the impact of these components on process measures – i.e. therapeutic relationship, treatment satisfaction and adherence than on clinical outcomes – i.e. symptoms and relapse. A small number of trials suggest that brief training courses and simple methods for structuring parts of clinical consultations can improve communication and subsequently clinical outcomes. Conclusions: Methodologically, rigorous research advancing current understandings of non-specific components may increase effectiveness across different treatments, potentially benefitting large numbers of patients. Brief training for clinicians and structuring clinical communication should be used more widely in practice.